First test Nosography Medical Contest - Monge, Carlos (1924)
To proceed with the order, I will deal first of which should be the spirit of teachers; then the basis and purpose of the course of Internal Pathology; following the criteria by which it should be studied, and finally the teaching method that suits their teaching.